Punitive justice in the Malaysian criminal law: balancing the rights of offenders with those of the victims - Hussin, Nasimah (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
It is undeniable that there has been a rise in the crime index cases in Malaysia. Statistics recorded showed that there were 984,789 criminal cases through the years 2005 until 2009, i.e. the average of 16413 cases per month and 547 cases per day. It can be interpreted from the statistics that if the crime rate is high, the number of the aggrieved parties who are affected by those criminal acts is also large. This is our main concern. The question arises as to what extent the punitive justice manages to resolve this problem. This paper discusses this scenario in the Malaysian context. It examines the extent of which the existing law guarantees the rights of the offenders and those of the victims. It clarifies whether they get fair and just treatment in the present criminal justice system.